Sarjana plan: public awareness of people in rural area towards the product / Siti Hasrina Mohamad Jamali - Mohamad Jamali, Siti Hasrina (2011)
Takaful is a Shariah compliant cooperative risk. Takaful is the oldest of insurance sharing (Dr. Muhammad Imran Usmani, 2007).The Grand Council of Islamic Scholars, Maja-al-Fiqh, only approved Takaful as a Sharia-acceptable alternative to traditional insurance in 1985, however restriction from Riba, Gharar and Maysir. Managing these requires some ingenuity and Chinese people represent towards Takaful products rather than insurance. Takaful is a broad and exciting global opportunity, offering way to capture currently underserved customer base. Takaful covers the whole range of insurance activities, from personal line, like household and motors; through to long-term savings, life protection, investment products, health care, corporate, trade and reinsurance Refer to the book “The Ready to use Sales Tools” provide by Etiqa, it stated that Sarjana Plan is one of their products. This product is a combining between coverage and saving and is an effort is to provide a special fund to their customer. This plan is build by Etiqa under Takaful brand is to helping people for make their life simple without combining “riba” or other else. This because, by having this plan, customer can make sure their child can further study in another level without having financial problem. Back to now day issue, we are hearing that so many student that making a loan with PTPTN not paying their loan back (Utusan Malaysia,2010).This matter becomes worse to other student when they want to making a loan with PTPTN. So that, PTPTN was making a strict rule to whom who want to get loan with them. But, for family that aware about this Etiqa plan they would not being worried because this plan can being use before 3 years from their maturity date to pay the fees, living expenses, books and others.Thus, customer can smile when they get know their child can enter into university with a proper strategic financial planning and coverage. This Etiqa Takaful Sarjana’s is comprehensive plans that must people have to their child future.